SINERGI: Human Resource Management Learning Innovation Using Website-Based Instructional Media - Nugroho, Fajar Wahyu; Rr Chusnu Syarifa Diah kusuma; Wahyu Rusdiyanto (Universitas Negeri Semarang, 2024)
Purpose: This research aims to determine the urgency of Human Resource Information System (HRIS) practicum and to develop the HRIS application as a human resource management learning innovation within the Vocational Faculty, Yogyakarta State University. Methods: This research is a Research and Development study designed to be a multi-year study using the ADDIE model approach. The ADDIE model is an abbreviation for the five stages of the development process, namely Analysis, Design, Develop, Implement and Evaluate. In the previous year, the researchers had completed the design of an HRIS to be used as a learning media. Design and construction focus on needs analysis and system design formulation (Analysis and Design). In the second year or the study, researchers begin to develop designs into product prototypes and trials (Development and Implementation). In the third year, the researchers focus on evaluation. Evaluation needs to be carried out to improve the system by processing data obtained from previous phases that have been carried out. So, this research uses the Research and Development method with ADDIE model over a multi-year basis. Result: The result of the study is the development and implementation of web-based HRIS for learning practices in human resource management courses for students. Novelty: The novelty of this research is to develop HRIS as an interesting and interactive learning media for all students to learn human resource management as a preparation for work later. The target output of this research is articles published in reputable international journals or proceedings as well as IPR for the HRIS products being developed.